Theorem 1.8 Let $(X,M,\mu)$ be a measure space

c.) (continuity from below) If $\{E_j\}_{1}^{\infty}\subset M$ and $E_1\subset E_2\subset\ldots$, then $\mu(\cup_{1}^{\infty}E_j) = \lim_{j\rightarrow \infty}\mu(E_j)$

A finitely additive measure $\mu$ is a measure if and only if it is continuous from below as in theorem 1.8c.

Proof: Let's assume $\mu$ is a finitely additive measure, and continuous from below. We want to show that $\mu$ is a measure. Suppose we have $\{E_j\}_{1}^{\infty}\subset M$. Set, $$F_k = E_k\setminus \Bigg[\bigcup_{1}^{k-1}E_j\Bigg] = E_k \cap \Bigg[\bigcup_{1}^{k-1}E_j\Bigg]^{c}$$ Then $F_k$'s are disjoint and belong to $M$, and $\cup_{1}^{\infty}F_k = \cup_{1}^{\infty}E_j$. By the continuity from below, $$\mu\Bigg(\bigcup_{1}^{\infty}E_j\Bigg) = \lim_{j\rightarrow\infty}\mu(E_j)$$ Since $\mu$ is finitely additive, and $E_1,\ldots,E_n$ are disjoint then $$\mu(F_k) = \mu\Bigg(\bigcup_{1}^{n}E_j\Bigg) = \sum_{1}^{n}\mu(E_j)$$ Hence $$\mu\Bigg(\bigcup_{1}^{\infty}E_j\Bigg) = \mu\Bigg(\bigcup_{1}^{\infty}F_k\Bigg) = \lim_{k\rightarrow\infty}\mu(F_k) = \lim_{n\rightarrow\infty}\sum_{1}^{n}\mu(E_j) = \sum_{1}^{\infty}\mu(E_j)$$ Therefore, $\mu$ is countably additive. If, $\mu$ is a measure, by theorem 1.8c, $\mu$ is continuous from below.

I am not sure if I am right, any suggestions would be greatly appreciated.


When you first you the continuity from below, the $E_j$ have to be an increasing sequence. You didn't assume this in the first place. After, you're writing:

$$\mu(F_k) = \mu\Bigg(\bigcup_{1}^{n}E_j\Bigg)$$. Where does this come from?

I suggest you simply define $$F_k=\bigcup_{1}^{k}E_j$$.

Clearly, $$\bigcup_{k\geq 1}F_k=\bigcup_{j\geq 1}E_j$$

Then, as $\mu$ is finitely additive, and as the $E_j$ are disjoint (you must assume this at the beginning of your proof), $$\mu\left(F_k\right)=\sum_{j=1}^k\mu(E_j)$$.

Now you can use the continuity from below, since $(F_k)$ is an increasing sequence of measurable sets:

$$\mu\left(\bigcup_{j\geq 1}E_j\right)=\mu\left(\bigcup_{k\geq 1}F_k\right)=\lim_{n\rightarrow +\infty}\mu(F_k)=\lim_{n\rightarrow +\infty}\sum_{j=1}^k\mu(E_j)=\sum_{j=1}^{+\infty}\mu(E_j)$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.